PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP PENDAPATAN PENJUALAN PT CAHAYA METAL INDO PERKASA - Rizky Eka Putra (EQUILIBIRIA, 2016)
This study was conducted to determine: (1) Effect of Inflation on PT Cahaya Metal Indo Perkasa during the period from January to December. (2) Effect of Exchange Rate on Light PT Cahaya Metal Indo Perkasa for a period of months from January to December .. (3) Effect of simultaneous Between Inflation and Exchange Rate to PT Cahaya Metal Indo Perkasa during the period from January to December. This study is quantitative in that it refers to the calculation of research data in the form of numbers. The variables of the study include the dependent and the independent variables. The sample in this research is PT Cahaya Metal Indo Perkasa -month period from January to December 2015. The sample selection using the method of reporting total sales, with a total of 12 (twelve) of data during the period from January to December 2015. Data were analyzed using regression analysis berganda.Berdasarkan Statistical analysis can be summed up the effect of inflation (X1) the correlation (1.658) and significant (0.004) 0.05. which means that the relationship is significant. Exchange Rate (X2) effect on sales revenue is the correlation (1.269) with a positive value indicates the direction of the relationship. Significant value (0.236) 0.05, which means the relationship is not significant. F count is (2089) with significant value 0.004 Fhitung lower than 0.05.Nilai significance 0.004 0.05 which means that the relationship is significant.